Insights into the oral microbiota in human systemic cancers - Su, Lan; Yang, Rui; Sheng, Yanan; Ullah, Saif; Zhao, Yuheng; Shunjiayi, Hu; Zhao, Zhuo; Wang, Qingjing (Frontiers in Microbiology, 2024)
The oral cavity stands as one of the pivotal interfaces facilitating the intricate interaction between the human body and the external environment. The impact of diverse oral microorganisms on the emergence and progression of various systemic cancers, typified by oral cancer, has garnered increasing attention. The potential pathogenicity of oral bacteria, notably the anaerobic Porphyromonas gingivalis and Fusobacterium nucleatum, has been extensively studied and exhibits obvious correlation with different carcinoma types. Furthermore, oral fungi and viruses are closely linked to oropharyngeal carcinoma. Multiple potential mechanisms of oral microbiota-induced carcinogenesis have been investigated, including heightened inflammatory responses, suppression of the host immune system, influence on the tumor microenvironment, anti-apoptotic activity, and promotion of malignant transformation. The disturbance of microbial equilibrium and the migration of oral microbiota play a pivotal role in facilitating oncogenic functions. This review aims to comprehensively outline the pathogenic mechanisms by which oral microbiota participate in carcinogenesis. Additionally, this review delves into their potential applications in cancer prevention, screening, and treatment. It proves to be a valuable resource for researchers investigating the intricate connection between oral microbiota and systemic cancers.